The Small-Scale Flow Field Around Dipsastraea favus Corals - Shavit, Uri; Mass, Tali; Genin, Amatzia (Frontiers in Marine Science, 2022)
Key biological processes that are related to feeding, growth, and mortality in corals and other benthic organisms, depend on the flow field around them. For example, in the absence of flow, oxygen is accumulated inside and around photoautotrophic organisms such as algae and corals, and the rate of photosynthesis is therefore reduced. When mixing by turbulence and by streamline separation is suppressed, nutrient supply is reduced and prey capture becomes insufficient. Despite the overwhelming ecological impacts of flow on corals, almost no in-situ studies focused on the hydrodynamics at the scale of the coral polyps and their tentacles. Here we report on in-situ measurements obtained by an underwater Particle Image Velocimetry (PIV) above the tentacles of the massive coral Dipsastraea favus. The tentacles in this species, approximately 5-10 mm long, extend during the night and contract during the day. A comparison was made between the flow field around the coral when the tentacles were contracted and extended. As in large-scale canopy flows such as forests or urban areas, we found that when the tentacles were extended, a mixing layer rather than a boundary layer was formed above the coral. Velocities in between the tentacles were reduced, resident time increased, and velocity instabilities developed around the tentacle tips. Our in-situ measurements under the conditions of contracted tentacles agreed well with laboratory measurements obtained above dead skeletons of D. favus. When the tentacles were extended, a velocity profile typical for canopy flows developed, having a clear inflection point near the interface between the tentacles and the layer of free flow. The relative velocity fluctuations increased up to 3.5-fold compared with the state of contracted tentacles. The highest mixing was around the distal ends of the tentacles, where knob-like spheres named acrospheres contain extremely high concentrations of nematocytes. The intense mixing, the ensuing slowing down of prey movement, and its longer residence time within that zone may augment prey capture by the coral. These findings can explain the ubiquitous occurrence of acrospheres in benthic cnidarians.